Building Information Modeling 2018
DOI: 10.1007/978-3-319-92862-3_15
|View full text |Cite
|
Sign up to set email alerts
|

Common Data Environment

Abstract: Building Information Modeling, as a model-based approach, has various implications for the information and data management of construction projects. In particular, data exchange during the planning and execution of BIM-based projects creates unique demands for the management of data, since the participants involved exchange different kinds of information at various levels of detail according to their individual requirements, and not just once but repeatedly and back and forth. To address this, procedures for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…The information delivery using BIM is defined in ISO 19650 [8], providing workflows for requesting and delivering information at certain points during the project delivery and asset operation. Applied to CDEs, workflows are proposed providing access rights to the data in certain status types [25]. The status types are Work in Progress, Shared, Published and Archived and the respective workflows, which transfer data from one status to another, require an approval procedure in each case [8].…”
Section: Workflow-driven Bim-based Collaborationmentioning
confidence: 99%
“…The information delivery using BIM is defined in ISO 19650 [8], providing workflows for requesting and delivering information at certain points during the project delivery and asset operation. Applied to CDEs, workflows are proposed providing access rights to the data in certain status types [25]. The status types are Work in Progress, Shared, Published and Archived and the respective workflows, which transfer data from one status to another, require an approval procedure in each case [8].…”
Section: Workflow-driven Bim-based Collaborationmentioning
confidence: 99%
“…Furthermore, BIM realisation can be achieved either by a single data model or a series of closely linked federated models [39]. However, Preidel et al (2018) indicated that direct utilisation of a single shared model is not recommended since it results in a complicated large model that can be hard to handle. On a similar subject, a collaboration between project stakeholders can be categorised into two main components: file-based collaboration or model-based collaboration.…”
Section: Developing Tools and Platforms For Data Exchangementioning
confidence: 99%
“…Hence, many BIM models are created in a given project by various stakeholders to achieve different objectives. Each of these models represents an individual part of the entire building, and it is called a domain-specific partial model [22]. Despite the different use of these sub-models, they share some commonalities that are not exclusive to a specific domain.…”
Section: Introductionmentioning
confidence: 99%
“…Hierarchical groups and the Branch-Publish functionality would clarify the modelling responsibilities between various disciplines and enable the validation of the work done by group members. Preidel, Borrmann, Mattern, König and Schapke (2018) present three states for the data: work in progress, shared and published. For transition to the next state, information checking or authorising is needed.…”
Section: Recommendations For Future Workmentioning
confidence: 99%
“…For transition to the next state, information checking or authorising is needed. Preidel et al (2018) also present the fourth state of archived for information that has been superseded, withdrawn or rejected during the data management. Hierarchical groups on the single shared model system could be a technique for implementing these four states.…”
Section: Recommendations For Future Workmentioning
confidence: 99%